Answer:
we need the question
Step-by-step explanation:
Answer:
6. (a-4)(a+9)
7. (3p+4)(p-2)
8. Will explain below.
9. (5b+4)(5b-4)
Step-by-step explanation:
HELLOOO IM BACK
6. -4*9 = -36 (the variable), 9-4 = 5 (a) , so a^2 +5a - 36 is fulfilled.
7. 4*-2 = -8, 4-2 = 2, so 3p^2 - 2p - 8 is fulfilled.
9. 25b^2 = (5b)^2
16 = 4^2
Using the difference of squares formula, a^2-b^2= (a+b)(a-b)
Answer:
v = -1
Step-by-step explanation:
First, you will need to solve it step-by-step:
(4v − 9)(1 + v) = 0
Next, you need to simplify both sides of the equation:
4v(2) − 5v − 9 = 0
Now, factor the left side of equation:
(4v − 9)(v + 1) = 0
The last thing you need to do is to set all of the factors to equal to zero:
4v − 9 = 0 or v + 1 = 0
So, that means that you answer:
v=9/4 or in your case, v = −1